Pemecahan Masalah Stagnasi Ekonomi Petani Karet Melalui Aktivasi Bumdes di Desa Atiran Kabupaten Hulu Sungai Tengah - Afifah, Siti; Hakim, Arif Rahman; Salasiah; Safitri, Erlinda Septia; Saputra, M. Rizky Yuanda; Damayanti, Rismi; Baihakki, Fajar; Zhafira, Ananda Salma; Bahran; Amalia, Nur; Riswanda, Noor Akhmad (Prodi Sosiologi FISIP ULM, 2025)
The lack of economic value of local commodities in Atiran Village, Batang Alai Timur sub-district, Hulu Sungai Tengah, is the background to the problem of economic stagnation experienced by the community. The team found that non-optimal commodity management, limited distribution channels and pest attacks are the main challenges that must be overcome so that local potential can be optimized. The lack of community knowledge about the added value of local commodities also worsened the condition. In an effort to answer these problems, the service team carried out 4 service activities, namely; (1) Mapping the root of the problem and potential; (2) Community awareness efforts; (3) Conducting discussions with the Department of Industry and Trade of Hulu Sungai Tengah Regency; and (4) Establishment of Village-Owned Enterprises (BUMDes). The goal of this program is to raise community awareness of the value and potential in local commodities and to achieve sustainable economic development. The four program activities were conducted using a people-centered development approach. People-centered development or community development is a way of development so that community involvement is more mature. The implementation of this service lasted for 57 days, starting from July 18, 2024 to September 12, 2024. The achievements of this program include increasing community awareness of the potential of local commodities and the economic value of local commodities, as well as the formation of Village-Owned Enterprises (BUMDes). With the cooperation between the village community and village officials as well as with related agencies, it can encourage the economic welfare of the Atiran Village community to achieve sustainable economic development, so that this village can be economically independent and can be more resilient in facing future challenges.